Providing psychological support to people impacted by terminal illness: A mixed methods study of hospice staff perceived competence, confidence and training needs - Fatema Zavery; Sulafa Fakhreddin; Sarah Huibregtse Van Loon; Mhairi McDougall; Anne Finucane (PLoS ONE, 2025)
Background Psychological distress is common amongst people with a terminal illness. While mental health specialists have a role in assessment and management of those with complex psychological problems, hospice clinicians provide psychological support to most patients and families. Aim To describe current practices relating to the provision of psychological support by hospice clinicians, and to explore perceived competence, confidence and training needs in relation to this aspect of their role. Design We used a parallel mixed methods research design. An online questionnaire consisting of closed and free-text questions was emailed to 273 hospices in the UK and the Republic of Ireland between May and June 2023. Setting/Participants Participants included nurses, doctors, and allied health professionals employed by a hospice. Quantitative data was analysed descriptively using SPSS 27, and free-text data was analysed thematically guided by the framework method. Results 151 hospice staff completed the questionnaire. Most (81%) reported that they regularly screen for psychological distress, but clinical judgement, as opposed to use of a validated screening tool, was most common. Respondents reported confidence and competence in many areas. Overall, 72% strongly agreed they were willing to explore difficult subject matter. However, only 25% strongly agreed they were confident in differentiating level of psychological need, and 36% reported they could not arrange appropriate psychological support when needed. Almost all (95%) agreed that training in psychological support would enhance their practice. Individual and family factors such as denial, communication challenges and family conflict were barriers to providing psychological support. Systemic factors were time constraints, prioritisation of physical symptoms and limited access to mental health specialists. Conclusion Hospice staff report that they are confident in providing basic psychological support. However, there was a desire for further training in this aspect of care. Clearer guidance on referral criteria for specialist psychological support is warranted.